Optimization of tool design parameters for thread tapping process of Ti-6Al-4V - KENTLİ, AYKUT (SAGE PUBLICATIONS LTD, 2021)
Thread tapping is one of the most important machining processes. Although thread tapping is a usual process and has been used for decades, the process still needs improvement for promising materials such as titanium alloys to increase the performance of the process. Titanium alloys are known as difficult-to-cut materials due to their low heat conductivity and elastic modulus. The aim of the work presented in this paper is to optimize the tapping tool primary design parameters for Ti-6Al-4V. The most influential tool design parameters on the process were selected as the rake angle, helical flute angle, chamfer angle, and tool coating. Optimization of the tool design parameters was made by considering the results of the experimental work. Two levels of each parameter were chosen. Taguchi L8 orthogonal array was used as the design of experiment. Tapping tool temperature and tapping torque were determined as the process outputs. According to the results, the optimized tool design parameters were found as 6 degrees rake angle, 12 degrees helical flute angle, 14 degrees chamfer angle, and TiCN coating.
Keywords: Thread tapping; torque; temperature; optimization; tool design